2022
DOI: 10.1016/j.jhealeco.2021.102575
|View full text |Cite
|
Sign up to set email alerts
|

God is in the rain: The impact of rainfall-induced early social distancing on COVID-19 outbreaks

Abstract: We measure the benefit to society created by preventing COVID-19 deaths through a marginal increase in early social distancing. We exploit county-level rainfall on the last weekend before statewide lockdown in the early phase of the pandemic. After controlling for historical rainfall, temperature, and state fixed-effects, current rainfall is a plausibly exogenous instrument for social distancing. A one percent decrease in the population leaving home on the weekend before lockdown creates an average of 132 doll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 60 publications
1
8
0
Order By: Relevance
“…Our study also showed that the rainy season has a positive effect on reduction of HFMD transmission (eTable 6 in the Supplement). This nding is similar with the ndings of previous studies in which the rainy season was reported to have likely reduced outdoor activities and social mixing (i.e., rainy season offered a social-distancing bene t against the epidemic) [30,31]. We found that these school-based measures had no signi cant impact on HFMD transmission in 2015 (associated reduction rate, 1.83%; 95% CI, − 0.58-4.28%).…”
Section: Discussionsupporting
confidence: 89%
“…Our study also showed that the rainy season has a positive effect on reduction of HFMD transmission (eTable 6 in the Supplement). This nding is similar with the ndings of previous studies in which the rainy season was reported to have likely reduced outdoor activities and social mixing (i.e., rainy season offered a social-distancing bene t against the epidemic) [30,31]. We found that these school-based measures had no signi cant impact on HFMD transmission in 2015 (associated reduction rate, 1.83%; 95% CI, − 0.58-4.28%).…”
Section: Discussionsupporting
confidence: 89%
“…The positive relationship between big firms and excess mortality due to COVID-19 seems to reinforce the idea that ambient air pollution can increase the severity of the disease. While the virtuous effect of historical rainy days can be explained considering the arguments put forward by Shenoy et al 107 , which argued that rainfall may lead to higher social distancing. This could have mitigated the negative impact of the outbreak.…”
Section: Resultsmentioning
confidence: 99%
“…If some studies found that temperature may increase the spread of COVID-19 8 , 101 , other research found a negative statistical association between the two variables 102 , 103 .While, there is a substantial consensus in the literature that warmer climate conditions may reduce COVID-19 mortality 103 105 and case-fatality rate 17 . Even if rainfall was not found to be an important predictive factor in COVID-19 spread and mortality in the most literature 106 , a recent paper pointed out that rainfall may lead to higher social distancing and help to mitigate the adverse effects of the outbreak 107 . The provinces with international borders, the share of foreign population, the province capital’s distance from the nearest airport, and the size of the province are used to control the effect of the movement of people.…”
Section: Datamentioning
confidence: 99%
“…16 All available hourly, population-weighted ERA5 and NLDAS values since January 1, 2020 were extracted, aggregated to daily mean or total values, and matched by date and district to the R t values. The following variables were included as the main exposures of interest based on their documented or hypothesized associations with SARS-CoV-2: near surface air temperature (°C) 32,33 ; relative humidity (%) 34 ; solar radiation (KJ/m 2 ) 35 ; total precipitation volume (mm) 36 ; average 10-m above ground wind speed (m/s). 37 In addition, average volumetric soil moisture (m 3 /m 3 ) was included as a negative control exposure 38 , since it is a variable presumed to affect infectious disease transmission through its influence on pathogen survival on surfaces and fomites 31 , which is thought to be at most only a secondary mode of SARS-CoV-2 transmission.…”
Section: Methodsmentioning
confidence: 99%